The lack of counselling and passively case detection affecting the occurrance of grade 2 disability in Sampang - Kamal, Muhammad; Martini, Santi (Faculty of Public Health, 2015)
ABSTRACTLeprosy is a chronic disease that affects the skin, peripheral nerves, even the other of body organs. This disease can also causing permanent disability that can affect to quality of life of sufferers. Sampang as the region with the highest average of PR in 2010-2014, it has leprosy grade 2 disability proportion which is 13%, in the other words that it is higher than the specified standard that is 5% or less. This study aimed to analyze the health service factors that affecting the occurrence of leprosy grade 2 disability. This study was an observational-analytic by using case control design. This study conducted in 8 administrative territory of community health center in Sampang. Sample were 33 type MB leprosy patients with grade 2 disability (case group) and 33 with grade 0 or grade 1 disability (control group). Sample has been taken by using simple random sampling technique. Data analysis was carried out simultaneously with multiple logistic regression. The results showed that the method of passive case detection (OR=7,005; 95% CI: 1,595-30,763), a very late diagnosis (OR=15,264; 95% CI: 1,469-158,594) ), lack of POD (OR=7,016; 95% CI: 1,574-31,274) and the lack of counselling (OR=8,241; 95% CI: 1,747-38,847) affecting the occurence of leprosy grade 2 disability. The conclusion that the passively case detection, a very late of diagnosis, the lack of POD and the lack of counseling affecting the occurrence of leprosy grade 2 disability at leprosy patients in Sampang. It is suggest to stakeholders to increase actively case detection, counselling.Keywords: disability, leprosy, case detection, counselling